Ultrafast Relaxation Dynamics and Nonlinear Response of Few‐Layer Niobium Carbide MXene. Issue 8 (11th May 2020) - Gao, Lingfeng; Chen, Hualong; Zhang, Feng; Mei, Shan; Zhang, Ye; Bao, Wenli; Ma, Chunyang; Yin, Peng; Guo, Jia; Jiang, Xiantao; Xu, Shixiang; Huang, Weichun; et al.
Abstract: As one of the rising 2D materials, niobium‐carbide (Nb2 C, well‐known as a member of MXene family) has attracted considerable attention owing to its unique physical and chemical properties. In this work, few‐layer Nb2 C nanosheets (NSs) with large (≈255 nm) and small (≈48 nm) lateral dimensions are obtained via a combination of selective etching and liquid cascade centrifugation. Their relaxation time and photophysics process are systematically investigated by transient absorption spectroscopy, and the size effect is demonstrated by phonon‐bottleneck mechanism. Ultrafast fast relaxation time (37.43 fs) and slow relaxation time (0.5733 ps) are observed due to the symmetric structure and metallicity of Nb2 C NSs. The nonlinear optical properties of Nb2 C NSs are studied by Z‐scan technique, and both saturable absorption and reverse‐saturable absorption are observed. According to first principle calculations, these phenomena can be attributed to the special band structure of Nb2 C near the Fermi level, where two‐photon absorption or multiphoton absorption may occur under the irradiation of long wavelength light. These intriguing results suggest that few‐layer Nb2 C NSs can be used as building blocks for broadband ultrafast photonics and optoelectronic devices and also hold the potential for breakthrough developments in these fields. Abstract : Few‐layer Nb2 C nanosheets with various lateral dimensions are synthesized via the combination of selective etching and liquid cascade centrifugation. The relaxation dynamics and nonlinear response of Nb2 C nanosheets are systematically investigated by transient absorption spectroscopy and Z‐scan technique, respectively. These intriguing phenomena can be well explained by the special band structure of Nb2 C, according to the first principle calculations.